Early evidence for capacity standardisation in Western Europe. The vessels from Mailhac (Aude, France) 9th-7th centuries BC - Thibaud Poigt; Alexis Gorgues; Antoine Dumas (PLoS ONE, 2025)
This paper presents an original study of the metrological characteristics of a series of vessels discovered in the necropolis of Le Moulin (Mailhac, southern France) and dated to the Late Bronze Age and the beginning of the Early Iron Age. A metrological study of the capacities of these artefacts is presented, based on a protocol of 3D modelling from 2D drawings to calculate the internal volumes of the vessels, and a series of mathematical and statistical analyses. The results make it possible to identify one of the earliest evidence for metrological practices based on capacity in Western Europe.